The Influence of Discipline and Work Motivation on Employee Performance at the Medan Amplas District Office - Juliana Putri; Siti Ummi Arfah Nasution; Zulaili Zulaili (LPPM Universitas Buddhi Dharma, 2025)
This study aims to determine whether work discipline and motivation have partial and simultaneous effects on employee performance at the Medan Amplas District Office. The population of this research consists of al employees at the office, totaling 32 individuals. The sampling technique used is saturated sampling (cencus), where all members of the populations are included inthe sample. Therefore, the sample in this study consists of 32 employees. The research employs a quantitive approach with several tests, including reliability analysis (comprising validity and reliability tests), classical assumption tests (including multicollinearity, autocorrelation, heteroscedasticity, and normality tests), as well as regression analysis, which includes multiple linear regression, t-test, F-test, and the coefficient of determination (R2) test. Based on the analysis of primary data using SPSS 22, the following multiple testing rules regression equation was obtained : Y=20.303+0.329X1+0.224X2+e. The hypothesis testing results show taht, partially, the work discipline variable (X1) has a positive and significant effect on employee performance, as indicated by the t-value being greater than the t-table value. The work motivation Variable (X2) also has a positive and significant effect on employee performance, evidanced by the t-value exceeding the t-table value. Simultaneously, work discipline and motivation have a significant influence on employee performance, as shown by the F-value being greater the F-table value. From these results, it can be concluded thar both work discipline and work motivation positively and significantly affect the performance of employees at the Medan Amplas District Office.